Performance of the HAS‐BLED, ORBIT, and ATRIA Bleeding Risk Scores on a Cohort of 399 344 Hospitalized Patients With Atrial Fibrillation and Cancer: Data From the French National Hospital Discharge Database - Daniele Pastori; Amélie Marang; Arnaud Bisson; Julien Herbert; Gregory Yoke Hong Lip; Laurent Fauchier (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background The association between cancer types and specific bleeding events in patients with atrial fibrillation has been scarcely investigated. Also, the performance of bleeding risk scores in this high‐risk subgroup of patients is unclear. We investigated the rate of any bleeding, intracranial hemorrhage, major bleeding, and gastrointestinal bleeding according to cancer types in patients with atrial fibrillation. We also tested the predictive value of HAS‐BLED, ATRIA, and ORBIT bleeding risk scores. Methods and Results Observational retrospective cohort study including hospitalized patients with atrial fibrillation and cancer from the French National Hospital Discharge Database (Programme de Medicalisation des Systemes d'Information) from January 2010 to December 2019. Major bleeding was defined according to Bleeding Academic Research Consortium definitions. Patients with HAS‐BLED ≥3, ATRIA ≥5, or ORBIT ≥4 were classified as at high bleeding risk. Receiver operating characteristic analysis for each score against any bleeding, major bleeding, gastrointestinal bleeding, and intracranial hemorrhage was performed. Areas under the curve (AUCs) were then compared. We included 399 344 patients. Mean age was 77.9±10.2 years, and 63.2% were men. The highest intracranial hemorrhage rates were found in leukemia (1.89%/year), myeloma (1.52%/year), lymphoma and liver (1.45%/year), and pancreas cancer (1.41%/year). Receiver operating characteristic analysis showed that ORBIT score predicted best for any bleeding. In addition, ORBIT score ≥4 had the highest predictivity for major bleeding (AUC, 0.805), followed by HAS‐BLED ≥3 and ATRIA ≥5 (AUCs, 0.716 and 0.700, respectively). HAS‐BLED and ORBIT performed best for intracranial hemorrhage (AUCs, 0.744 and 0.742 for continuous scores, respectively), better than ATRIA (AUC, 0.635). For gastrointestinal bleeding, ORBIT ≥4 had the highest predictivity (AUC, 0.756), followed by the HAS‐BLED ≥3 (AUC, 0.702) and ATRIA ≥5 (AUC, 0.662). Conclusions Some cancer types carry a greater bleeding risk in patients with atrial fibrillation. The identification and management of modifiable bleeding risk factors is crucial in these patients, as well as to flag up high bleeding risk patients for early review and follow‐up.